A novel CLTC‐FOSB gene fusion in pseudomyogenic hemangioendothelioma of bone. Issue 1 (22nd August 2020) - Bridge, Julia A.; Sumegi, Janos; Royce, Thomas; Baker, Michael; Linos, Konstantinos
Abstract: Pseudomyogenic hemangioendothelioma, an uncommon mesenchymal neoplasm composed of plump spindled and/or epithelioid endothelial cells, may present multicentrically and tends to locally recur but rarely metastasizes. Morphologic resemblance to epithelioid sarcoma and other spindle cell neoplasms may result in diagnostic confusion. Molecular characterization of pseudomyogenic hemangioendothelioma has revealed these neoplasms often harbor a rearrangement of the FOSB gene with SERPINE1 or ACTB as recurrent fusion gene partners. Herein, a case of a fibular pseudomyogenic hemangioendothelioma with minimal extension into the adjacent soft tissue arising in a 17 year‐old male is presented. The neoplasm exhibited sheets of epithelioid cells with abundant eosinophilic cytoplasm and variably eccentric nuclei. RNA sequencing revealed a novel CLTC‐FOSB fusion transcript that was subsequently confirmed by direct sequencing of reverse transcription‐polymerase chain reaction products demonstrating an in‐frame fusion between exon 17 of the clathrin heavy chain ( CLTC ) gene and exon 2 of the FOSB (FosB proto‐oncogene, AP‐1 transcription factor subunit) gene. CLTC‐FOSB fusion has not been described in a neoplasm before.